C66. Paraaortic abscess complicating an Aerococcus Viridans Endocarditis: A Case Report. (23rd November 2021) - Farissa, I P; Goma, M S; Permitasari, D A; Nugroho, M A
Abstract: Background: Infective Endocarditis (IE) associated with high mortality and complication despite improvement in its management. Paravalvular abscess known as feared complication of IE because its association with increased mortality. We describe a case of man with paravalvular abscess complicating IE undergone Aortic Valve Replacement. Case Summary: A 42 years old man presented with exertional dyspneu since 2 weeks prior to admission, exaggerated with mild activities, accompanied with nausea, vomiting, swollen legs, and subfebrile for weeks. He was conscious and moderately ill with pressure 100/50 mmHg, regular pulse of 70, respiratory rate 25 times/minute, temperature was 37˚C, oxygen saturation was 94% on room air with end diastolic murmur grade II/4 in right upper sternal border. The laboratory result was leucocytosis (12.900/cu mm). The echocardiography revealed calcified in RCC and NCC aortic valve, RCC prolapse, severe aortic insufficiency, hyperechoic in paravalvular area. MSCT Cardiac revealed fistula originating from aortic root to a sac led to left ventricle. Sensitivity cultured revealed Aerococcus viridans. We gave antibiotics for 3 weeks before he undergone Aortic Valve Replacement. 1 month follow up, he had no more symptoms, and the prosthetic valve was normal. Discussion: The diagnostic of IE remains challenging. It may present as an acute, rapidly progressive infection, but also as a subacute or chronic disease. Its complications need to be monitored vigilantly because it worsens the outcome. Antibiotics use for microbial eradication contributed by removing infected material surgically, might improve successful treatment for IE.